Freebies, freedom and fundamental change: resistance to neoliberal environmentalism in large "green" corporations. Issue 5 (4th May 2017) - Swaffield, Joanne
ABSTRACT: Despite the professed concern of many governments, businesses and individuals – and the recent publication of another alarming report from the IPCC – inaction on climate change remains a significant concern. For many, the problem is rooted in a neoliberal account of social change. Neoliberal environmentalism is the dominant approach to environmental issues but it is often blamed for the continuing failure of climate change policy in general and behaviour change initiatives in particular. This paper explores the dynamics of this dominant discourse through an examination of environmentalism in the large "green" corporation. Specifically, it uses discourse analysis to investigate so-called "climate champion" schemes and considers examples of resistance to the dominant neoliberal discourse. The paper finds that many of the champions did resist the basic components of neoliberal environmentalism. They challenged the principles of self-interest, self-rule and incremental change, and they talked about the possibility of enforced action. However, this resistance was limited in a number of different ways. The paper suggests that the workplace does play a role in restricting resistance but that there are more fundamental issues that need to be addressed if we hope to pursue an alternative approach to environmental problems such as climate change.